What is an arousal and how should it be quantified? - Davies, R; Bennett, L; Stradling, JR (1997)
Pathologically severe daytime sleepiness is one of the main symptoms seen in a respiratory sleep clinic and is due to repeated arousal from sleep. Which types of arousal are most important in causing this is uncertain and most studies have only found loose relationships between indices of arousal frequency and the severity of the ensuing daytime sleepiness. Recent attempts to improve these disappointing correlations have concentrated on detecting more minor arousal events through the use of novel EEG signal analysis techniques and non-EEG based signals such as blood pressure and heart rate. To date there are no good data sets which allow the relative merits of these various techniques to be compared and it is unclear whether these efforts to increase the sensitivity of arousal detection will lead to improvements in the clinical usefulness of sleep fragmentation scoring. Studies which relate both the traditional indices of sleep fragmentation and the newer methodologies to clinically relevant reference standards (such as measured excessive daytime sleepiness) are needed to clarify these issues.